2014
DOI: 10.1007/s10704-014-9971-3
|View full text |Cite
|
Sign up to set email alerts
|

Finite element simulations of notch tip fields in magnesium single crystals

Abstract: Recent experiments using three point bend specimens of Mg single crystals have revealed that tensile twins of {1012}-type form profusely near a notch tip and enhance the fracture toughness through large plastic dissipation. In this work, 3D finite element simulations of these experiments are carried out using a crystal plasticity framework which includes slip and twinning to gain insights on the mechanics of fracture. The predicted load-displacement curves, slip and tensile twinning activities from finite elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It is also known that intense basal slip within thin contraction twins result in shear localization regions where cracking may occur [14,30,31]. While extension twins have also been shown to promote cracking along their boundaries [8,[32][33][34], some works have indicated them as toughening agents as well [10,35]. Ductile damage through void growth is driven by matrix plasticity, which occurs in Mg by slip and twinning.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that intense basal slip within thin contraction twins result in shear localization regions where cracking may occur [14,30,31]. While extension twins have also been shown to promote cracking along their boundaries [8,[32][33][34], some works have indicated them as toughening agents as well [10,35]. Ductile damage through void growth is driven by matrix plasticity, which occurs in Mg by slip and twinning.…”
Section: Discussionmentioning
confidence: 99%
“…The manifestation of twinning is a large local lattice rotation to enable the activation of twin planes in order to accommodate slip. Whilst studies on magnesium by Kaushik et al [15,16] show the importance of twinning on deformation local to a crack tip, it is however ignored in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of anisotropy effects at the crack tip was recently investigated by Kartal et al [10] to evaluate the effects of crystallographic orientation and grain morphology on crack tip stress state and found that single crystal crack tip stresses largely remain independent of crystal orientation but that the plastic zone size and shape depends greatly upon it. Further studies include that by Biswas and Narasihman [11,12] who investigated crack tip fields in rate sensitive FCC single crystals; Lopez-Crespo et al [13,14] who address overload effects during fatigue crack growth in steel using synchrotron x-ray diffraction for both plane strain and stress conditions, and studies by Kaushik et al [15,16] on experimental and finite element simulations of notch tip fields in magnesium single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…This correlates with the absence of TTs in a small region near the notch root in their experiments. From finite element analysis, Kaushik et al [37] have noted that in the notched three point bend Mg single crystal specimen corresponding to the above orientation, the plastic hinge forms close to the notch root in the uncracked ligament. In other words, the normal stress on the plane ahead of the notch root changes from tensile to compressive beyond the hinge point which triggers TTs.…”
Section: Origin Of Tensile Twinning Near the Notch Rootmentioning
confidence: 99%